Literasi Keagamaan Katolik dan CharacterBuilding Peserta Didik Sekolah Menengah Kejuruan “Barries and Challenges” - Tobing, Ona Sastri Lumban; Astuti, Florentina Dwi; Handayani, Exnasia Retno Palupi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research based on the problems about catholic religion literacy, impact, obstacles and challenges toward students’ character building in vocational school. This research aimed to be solution for Catholic religion literacy at school which bring impact to the students’ character building at vocational school in Pontianak. The method used in this research was descriptive qualitative. The sources of the data were primary data, they were the result of interview and the secondary data were the result of observation of Catholic religion literacy. The finding of the researchs howed the process of Catholic religion literacy started from some stages, start from the schedule of Catholic religion literacy, time and place of literacy activity, and the people involve in the literacy activity and the media used. The literacy activity such as reading activity, material session, and catholic religion literacy assessment. The religion literacy at vocational school brought good impact to the students. The result of the religion Catholic activity raised the reading interest, found the source of religion references on the media, and gave impact toward students’ character building to be better.